PERAN DIPLOMASI BUDAYA DALAM MEWUJUDKAN KOMUNITAS SOSIAL-BUDAYA ASEAN: KASUS VIETNAM - Van Kim Hoang Ha (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2016)
In the era of globalization and international integration, international relationships is an integral part in foreign policy. So that the foreign policy conducted well, all countries must implement diplomacy. Cultural diplomacy is not only the application, the empowering culture to improve the behavior of diplomacy, but also the diplomacy using to respect and preserve the culture. The reality and the implementation of the Vietnam government and Party in recent years will mostly contribute to answer it. From here, the importance of cultural diplomacy in the process of establishing ASEAN Community 2015 will be seen as well. Cultural diplomacy not only improves the position and the authority of Vietnam in the international arena, but also strengthens the relations with other countries and contributes to the formation of ASEAN Social-Cultural Community in particularly and ASEAN Community 2015 in general. Keywords: Vietnam, cultural diplomacy, ASEAN Social-Cultural Community